Perkembangan Kewenangan Mengubah Undang-Undang Dasar di Indonesia - Jajang Indra Fadila (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2014)
Abstract: The development of Constitution Authority Changing in Indonesia. Since the beginning of the independence of Indonesia, the authority to change the Constitution set out in the 1945 Constitution is the People's Consultative Assembly (MPR). In its journey, Indonesia has experienced several changes in the Constitution 1945 changes into the constitution RIS jointly conducted by the government of the Central Indonesian National Committee (KNIP) as well as the formation of the Provisional Constitution of 1950. In addition, a constituent did drafting a new constitution, although in the end is not resolved. Constitution changes occurred back in the era of reforms undertaken by the Assembly, and further stipulate that the authority to change the Constitution and establish the institution is located in the MPR. Absrak: Perkembangan Kewenangan Mengubah Undang-Undang Dasar di Indonesia. Sejak awal kemerdekaan Republik Indonesia, kewenangan mengubah Undang-Undang Dasar telah ditetapkan dalam UUD 1945 adalah oleh Majelis Permusyawaratan Rakyat (MPR). Dalam perjalanannya, Indonesia mengalami beberapa kali perubahan Undang-Undang Dasar. Perubahan UUD 1945 menjadi konstitusi RIS dilakukan oleh pemerintahan bersama Komisi Nasional Indonesia Pusat (KNIP) begitu juga dengan pembentukan UUDS 1950. Sempat ada konstituante yang melakukan penyusunan UUD baru, meskipun pada akhirnya tidak terselesaikan. Perubahan UUD terjadi kembali pada era reformasi yang dilaksanakan oleh MPR dan selanjutnya menetapkan bahwa kewenangan mengubah dan menetapkan UUD adalah berada pada lembaga MPR. DOI: 10.15408/jch.v1i1.1458